Synthesis, Study and Utilization of Natural Products - Drasar, Pavel B. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Natural products and the preparations based on them play a stable and ever-increasing role in human and veterinary medicine, agriculture, in food and the cosmetic industry, and in an increasing number of other fields. Their importance is based on the fact that they are mostly bound to renewable sources, which in fact makes them valuable within a circular economy, inter alia. At the same time, natural products provide the origin of stereochemistry, optical activity, regioselectivity, chirality, and many other concepts and directions within science, development, and industry in a scope, which is indispensable. They serve as a constant powerful stimulus and model that inspires researchers to create new effective tools, similar to natural ones, for controlling bioregulation mechanisms and solving practical problems. This was the reason for organizing this Special Issue aimed at underlining the current developments in all the fields connected to natural products.